KPT prihatin madani (KRIS) mobile clinic lorry launched to strengthen community healthcare outreach - Ismail, Ilham Ameera (Faculty of Medicine, 2026)
A symbolic key handover ceremony for a specially converted lorry functioning as a mobile clinic was held on 27 January 2026, marking a significant milestone in strengthening community healthcare outreach programmes led by the Hospital Al-Sultan Abdullah (HASA), Universiti Teknologi MARA (UiTM). The key handover was officiated by the Minister of Higher Education, Dato’ Seri Diraja Dr Zambry Abd Kadir, to the Vice Chancellor of UiTM, Prof. Datuk Ts. Dr. Shahrin Sahib, with the attendance of the Deputy Director of Clinical Services, HASA, Professor Dr. Ahmad Izuanuddin Ismail, the Dean of the Faculty of Medicine, Professor Dr Fazah Akhtar Hanapiah and the hospital management.